PERAN CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING FINANCING RATIO (NPF), DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA PERIODE 2015-2020: (Studi Pada Perbankan Umum Syariah Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2020) - Sifa Khoirun Agustin; Irma Citarayani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Financing Ratio (NPF), and Financing to Deposit Ratio (FDR) on Sharia Banking profitability (Return On Assets) for the 2015-2020 period. The research method used in this research is quantitative research. This quantitative method is used to answer research problems related to numerical data and statistical programs. The data analysis method used in this research is multiple linear regression analysis with classical assumption test and hypothesis testing through SPSS 24. From the results of the coefficient of determination test or R Square, the value is 0.772 or means that the independent variable affects the dependent variable by 77% while the other 33% influenced by other variables. The results of the t test show that the Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) have a negative and significant effect on the company's profitability (Return On Assets) while the Non-Performing Financing Ratio has no effect on the company's profitability (Return On Assets). Based on the F test, it is concluded that the variables of Capital Adequacy Ratio (CAR), Non Performing Financing Ratio (NPF), and Financing to Deposit Ratio (FDR) simultaneously affect the profitability (Return On Assets) of Sharia Banking companies.